Dissociative chemisorption of hydrogen molecules on defective graphene-supported aluminium clusters: a computational study - Kumar, Deepak; Govindaraja, Thillai; Krishnamurty, Sailaja; Kaliaperumal, Selvaraj; Pal, Sourav (Physical Chemistry Chemical Physics, 2018)
Using periodic density functional theory-based calculations, in the present study, we address the chemical bonding between aluminium clusters (Al-n, n = 4-8 and 13) and monovacant defective graphene. The adsorption strength of the above-mentioned aluminium clusters is fivefold (approximate to 3 to 5 eV) higher on defective graphene as compared to the earlier reported values on non-defective graphene and BN-doped graphene. The Bader charge analysis and different charge densities reveal that this adsorption is driven by significant charge transfer from the Al clusters to defective graphene. Thus, chemisorbed Al clusters demonstrate high activity towards dissociative adsorption of molecular hydrogen.

Probing the catalytic activity of pristine and doped Pd and Ni metal clusters towards H2O molecule - Samal, Pragnya Paramita; Joshi, Krati; Kaliaperumal, Selvaraj; Krishnamurty, Sailaja (Computational and Theoretical Chemistry, 2019)
Electrolysis of H2O to produce molecular hydrogen, the most environment friendly and energy efficient fuel, using cost effective catalysts is one of the major global research challenges. To date, Pt remains the best suitable and yet highly expensive electro-catalyst for hydrogen evolution reaction. Design of an alternative cost-effective catalyst requires a fundamental molecular level understanding of the water molecule adsorption and its activation. In that context, we examine the adsorption and activation of water molecule on model alternative catalysts namely, Ni-6 and Pd-6 clusters using density functional theory based methodology. Ni-6 and Pd-6 clusters and their singly doped counterparts are used for this study. Mo, W, Fe, Co and Cu are used as doping elements. To quantify the influence of medium (neutral and alkaline) on the activation of the water molecule, Ni based clusters are considered in neutral and anionic states, respectively. The activity of these clusters towards H2O molecule is evaluated in terms of the adsorption energy, charge transfer, bandgap, red shift in O-H stretching frequency and dissociation barriers for H2O. The studies demonstrate that doping with Co in all the studied clusters (Pd-6, Ni-6 and anionic Ni-6) increases their activity. Best activity is noted for Fe doped neutral Ni b clusters with a dissociation barrier of 5.76 kcal/mol.
Keywords: Activation barrier; Ni clusters; O-H activation; Pd clusters; Red shift of O-H stretching frequency; Water adsorption

Graphene-based frustrated Lewis pairs as bifunctional catalysts for CO2 reduction via the dissociative chemisorption of molecular H-2: a periodic density functional perspective - Senthamaraikannan, Thillai Govindaraja; Krishnamurty, Sailaja; Kaliaperumal, Selvaraj (New Journal of Chemistry, 2021)
Nanocarbon-based frustrated Lewis pair (FLP) bifunctional catalysts, on account of their unquenched electron transfer property, are becoming increasingly attractive as catalysts for the CO2 reduction reaction via the dissociative chemisorption of H-2. In the present study, we propose a nanocarbon-based FLP catalyst. The pair comprises nitrogen doped/phosphorus doped graphene as Lewis bases and M(C6F5)(3) (M = B, Al, Ga, and In) as Lewis acids. The computational investigation reveals that the carbon atoms adjacent to the doped N and P atoms are the active sites towards the dissociative chemisorption of hydrogen molecule. The analyses of the Bader charges and difference charge densities validate the dissociative chemisorption of H-2 molecule and the fact that a significant electron redistribution promotes the polarization of the hydrogen molecule. Density of states confirms the hybridization between the p-states of the nitrogen/phosphorus atom and the s-state of hydrogen atom in all FLPs. The dissociative chemisorption of hydrogen is noted in all FLP complexes, thereby facilitating a low barrier reaction path for CO2 reduction. Between P-doped and N-doped FLPs, N-doped FLP catalysts prove to be a more promising counterpart with considerably low activation barriers, ranging between 0.01 and 0.11 eV, towards CO2 reduction. Thus, the present study demonstrates the great potential of doped carbon-based FLPs as novel nanostructure catalysts for CO2 reduction via the direct utilization of molecular hydrogen.

Role of chemical structure of support in enhancing the catalytic activity of a single atom catalyst toward NRR: a computational study - Senthamaraikannan, Thillai Govindaraja; Kaliaperumal, Selvaraj; Krishnamurty, Sailaja (Frontiers in Chemistry, 2021)
Using the periodic density functional theory–based methodology, we propose a potential catalytic system for dinitrogen activation, viz., single metal atoms (Mo, Fe, and V) supported on graphene-based sheets. Graphene-based sheets show an excellent potential toward the anchoring of single atoms on them (Mo, Fe, and V) with adsorption energies ranging between 1.048 and 10.893 eV. Factors such as defects and BN doping are noted to enhance the adsorption energies of single metal atoms on the support. The adsorption of a dinitrogen molecule on metal atom–anchored graphene-based supports is seen to be highly favorable, ranging between 0.620 and 2.278 eV. The adsorption is driven through a direct hybridization between the d orbitals of the metal atom (Mo, Fe, and V) on the support and the p orbital of the molecular nitrogen. Noticeably, BN-doped graphene supporting a single metal atom (Mo, Fe, and V) activates the N2 molecule with a red shift in the N–N stretching frequency (1,597 cm−1 as compared to 2,330 cm−1 in the free N2 molecule). This red shift is corroborated by an increase in the N–N bond length (1.23 Å from 1.09 Å) and charge transfer to an N2 molecule from the catalyst.

Unleashing methylammonium-guanidinium lead iodide hybrid perovskite spherulitic microstructures: a structural and morphological investigation - Mukul, Monika; Kaliaperumal, Selvaraj; Rani, Mamta; Tripathi, Surya Kant (MRS Communications, 2023)
Perovskites can offer an attractive replacement option for existing commercial solar technologies. Herein microstructure plays an important role in improving the efficiency and stability of solar cells. Previously unidentified spherulitic microstructures of self-assembled polycrystalline perovskites are explored in this report. For this an intermediate phase of a promising guanidinium (GUAI)-rich perovskite has been investigated for its structural and morphological properties. This study infuses new insight into the evolution of perovskite microstructure from heterogeneity to homogeneity, as a result unravels the structure of perovskite embryonic spherulites, lamellar arrangements, transcrystalline nature, novel spherulites bridging, hole nucleation, impingement, and defects.
Keywords: Microstructure; Morphology; Nucleation & growth; Perovskites; Phase transformation; X-ray diffraction (XRD)